Impact of the COVID-19 pandemic on the National Telehealth Service for triage and referral in Sweden: a national retrospective observational study - Johanna Berg; Jens Wretborn (BMJ Open)
Objectives Telehealth, the provision of healthcare through digital communication, has been proposed as a potential solution to meet the increasing demand for healthcare, particularly in the setting of the COVID-19 pandemic. Sweden has an established national telehealth service for triage and referral by phone (1177) since 2013 which has the potential to meet this increasing demand. However, little is known about the development and retention in demand during and after the pandemic in Sweden. The objective of this study was to investigate the utilisation of the national telehealth service in Sweden before, during and after the pandemic in relation to emergency department (ED) visits.Methods This was a retrospective observational study of telephone calls to the national telehealth service in Sweden. We collected the number of calls, number of answered calls and visits to ED in Sweden from 2017 through 2021, aggregated by month. The difference in number of calls and visits was analysed using Student’s t-test for related samples.Results Data were collected from all 21 healthcare regions in Sweden, serving 10.5 million citizens. The average number of monthly calls was 48 (SD 10) calls per 1000 citizens. The first month of the pandemic, March 2020, had the highest monthly calls per capita during the whole study period: 62 (diff 14, 95% CI 9 to 19, p<0.001). During the first 3 months of the pandemic, monthly calls increased by 22% (52.7 vs 43.2) compared with 2019 (diff 9.5, 95% CI −28 to –9, p=0.17). There was a 17% increase in calls for the whole year of 2020 compared with 2019 (49.2 vs 41.9, diff 7.3, 95% CI 3 to 11, p=0.002). Capacity, defined as the answer ratio, showed a negative correlation with demand (r=0.75, p<0.001).Conclusion The increase in calls to the national telehealth service during the first year of the COVID-19 pandemic suggests that the community will turn to a telehealth system in a healthcare crisis. The lack of capacity to meet the increasing demand may limit the effects of the telehealth service on the healthcare system as a whole.